2016
DOI: 10.1115/1.4032069
|View full text |Cite
|
Sign up to set email alerts
|

Guide-Vane Closing Schemes for Pump-Turbines Based on Transient Characteristics in S-shaped Region

Abstract: During the transitional processes of load rejection in a pumped-storage station, the S-shaped characteristics of the pump-turbines can result in relatively large water-hammer and pulsating pressures. These pressures and the high runaway speed during transient processes may directly damage the penstocks and shorten the life of the turbine. In this study, different guide-vane closing schemes for reducing the maximum transient pressures, including the water-hammer and pulsating pressures, and runaway speed were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…OGVCS plays an important role in ensuring the security and stability of the power grid, and several methods have been proposed to deal with the OGVCS problem. Based on the characteristics of the rigid watercolumn pressure during the transient process, Ref [10] proposed a two-phase guide-vane closing scheme and three-phase valve-closing schemes to control the pulsating pressures and the runaway speed. Ref [11] analysing the effect of valve closure on the water-hammer pressure and laid the theoretical foundation for improving the turbine guide-vane closure.…”
Section: Of 26mentioning
confidence: 99%
“…OGVCS plays an important role in ensuring the security and stability of the power grid, and several methods have been proposed to deal with the OGVCS problem. Based on the characteristics of the rigid watercolumn pressure during the transient process, Ref [10] proposed a two-phase guide-vane closing scheme and three-phase valve-closing schemes to control the pulsating pressures and the runaway speed. Ref [11] analysing the effect of valve closure on the water-hammer pressure and laid the theoretical foundation for improving the turbine guide-vane closure.…”
Section: Of 26mentioning
confidence: 99%
“…In the associated transient processes of pump-turbines, the S-shaped characteristics of the performance curves in turbine mode usually induce instability problems. The most common problems are difficulties in synchronizing with power grids during turbine start-ups, and unstable performance during turbine load rejections [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Detail theoretical analyses of guide vane closing scheme considering the pump turbine S-shaped characteristics were conducted in the paper [13]. Here, three types of closing schemes (shown in Fig.6) based on the theory were compared through experiments.…”
Section: Load-rejection Tests With Different Guide Vane Closing Schemesmentioning
confidence: 99%
“…Due to the S-shaped characteristics, the dynamic processes of a pumped storage station is complicated: 1) The unstable pump turbine S-shaped characteristics make it difficult to measure the Sshaped curves, which can, therefore, be obtained by the transient method [9,10]; 2) pump turbines often show an unstable runaway and no-load operations, which are close to the form of S-shaped curves [5][6][7][8]; 3) in the load rejection process, the water-hammer pressure is also related to the Sshaped curves; 4) in some extreme conditions, such as OAA load rejections, numerical simulations have shown that the water-hammer pressure, especially in the draft tube, is fairly significant [11,12]; 5) to control the water-hammer pressure and runaway speed during the load rejection process, multiphase closing schemes can be used to guarantee the safety of a pumped storage station [13]. Therefore, based on the transient issues described above, the relevant verification experiments were conducted to clarify the effects of S-shaped characteristics on hydraulic transients.…”
Section: Introductionmentioning
confidence: 99%